Have questions about your preparation or an upcoming test? Need help modifying the Study Plan to meet your unique needs? No problem. Just book a Skype meeting with Brent to discuss these and any other questions you may have.

- Video Course
- Video Course Overview
- General GMAT Strategies - 7 videos (free)
- Data Sufficiency - 16 videos (free)
- Arithmetic - 38 videos
- Powers and Roots - 36 videos
- Algebra and Equation Solving - 73 videos
- Word Problems - 48 videos
- Geometry - 42 videos
- Integer Properties - 38 videos
- Statistics - 20 videos
- Counting - 27 videos
- Probability - 23 videos
- Analytical Writing Assessment - 5 videos (free)
- Reading Comprehension - 10 videos (free)
- Critical Reasoning - 38 videos
- Sentence Correction - 70 videos
- Integrated Reasoning - 17 videos

- Study Guide
- About
- Office Hours
- Extras
- Prices

## Comment on

Find the Ratio a:b:c## in regards to statement 1.

## Once we know that the a:b:c

Once we know that the a:b:c ratio is equal to c/3 : c/2 : c, we can create an equivalent ratio that eliminates the fractions. We create that equivalent ratio by multiplying all three values by 6 (the least common multiple of 2 and 3) to get 2c : 3c : 6c

This is no different than taking the ratio 1 : 2 and multiplying both values by 5 to get the equivalent ratio 5 : 10

Does that help?

## i don't understand the second

and how can i say insufficient

## For statement 2, we're told

For statement 2, we're told that c = 6 AND ab = c

In other words, ab = 6

So, when we test certain values of a, b and c, those values must meet the given conditions.

NOTE: The values I used are not the only values meet the given conditions. We COULD have used other values. Here are some examples:

a = 1, b = 6, c = 6 (a:b:c = 1:6:6)

a = 0.5, b = 12, c = 6 (a:b:c = 0.5:12:6)

a = 4, b = 1.5, c = 6 (a:b:c = 4:1.5:6)

a = 3, b = 2, c = 6 (a:b:c = 3:2:6)

Notice that the ratio a:b:c is different each time. So, using the information in statement 2, we cannot answer the target question with certainty.

Does that help?

## What is the target question

## The target question for both

The target question for both statements is "What is the ratio a:b:c?

## Thank you gmat-admin, your

## That's correct.

That's correct.

## for statement 1, you can also

## The ratios 2:3:6 and 4:6:12

The ratios 2:3:6 and 4:6:12 are equivalent. So, there is still only one answer to the target question.

## For 1), How do we know c is

## For statement 1, we are

For statement 1, we are trying to rewrite the variable in terms of c.

So, for example, we rewrote a as a = c/3

Likewise, we rewrote b as b = c/2

Now comes c. What do we do with that? Well, since our goal is to rewrite each variable in terms of c, we can see that c is ALREADY written in terms of c. That is, c = c.

So, we're done!

Does that help?

## I can't believe I got this

## That's great to hear! Thanks

That's great to hear! Thanks for saying that.

## Hi,

why doesn't this method work?

c/a = 3/1 (cross multiply) to get 3a = C ie, ratio of 3;1???

thanks

## What relationship do you feel

What relationship do you feel has a ratio of 3:1?

If you feel that, since 3a = c, then the ratio a:c = 3:1, this is not correct.

We can verify this by examining some values of a and c that satisfy the equation 3a = c

One such solution is a = 1 and c = 3, in which case a : c = 1 : 3

Another such solution is a = 2 and c = 6, in which case a : c = 2 : 6 = 1 : 3

Etc

Does that help?

## Hi Brent,

Is this solution for the question in the video correct, my concern is Statement1 only:

Statement1:

c/a = 3, --> c:a =3:1

c/b=2 --> c:b = 2:1

c is the common, so let's make it equal in both rations

multiply by 2, c:a = 6:2 and c:b = 6:3

so a : b : c = 2 : 3: : 6

Statement 1 is Suff.

Statement 2 is not Suff.

Thanks

Aladdin

## That's a perfect solution,

That's a perfect solution, Aladdin!

## Is there anything wrong with

C/A = 3/1 and C/B = 2/1 so you have C:A 3:1 and C:B 2:1 convert to common C and get C:A = 6:2 C:B = 6:3 so your ratio is 2:3:6.

I guess my question is, am i wrong in assuming in the original that:

C = 3 and C = 2

A = 1 and B = 1

Does that make sense?

## That approach totally works

That approach totally works with this question.

The only thing I'd add is that, if C/A = 3/1, then it's quite possible that C = 3 and A = 1.

So, using those values in your solution will yield the correct answer.

That said, if C/A = 3/1, then it's ALSO quite possible that C = 6 and A = 2.

So, using those values in your solution will ALSO yield the correct answer (as will C = 12 and A = 4, etc)

Cheers,

Brent

## hi Brent,

Could you help me with the below question?

The monthly savings of a person is two fifths of his monthly salary. If his monthly salary is increased by 7/13th and his expenditure remains unchanged, then what will be ratio of new savings to old savings?

## Let M = ORIGINAL monthly

Let M = ORIGINAL monthly salary.

Since he saves 2/5 of his salary, the amount saved = 2/5 of M

= 2M/5

ASIDE: this also tells us that he SPENDS 3/5 of his salary (M).

So his monthly EXPENDITURES = 3M/5

------------------------

If his monthly salary increased by 7/13, then the NEW salary = M + (7/13 of M)

= M + (7M/13)

= 13M/13 + 7M/13

= 20M/13

Since his expenditures remain at 3M/5, the NEW amount saved = 20M/13 - 3M/5

= 100M/65 - 39M/65

= 61M/65

------------------------

Ratio of NEW savings to OLD savings = (61M/65)/(2M/5)

= (61M/65)(5/2M)

= 305M/130M

= 61/26

Answer: 61/26

## hi Brent, thank you for

the options i have are :

a) 26:61

b) 23:41

c) 26:41

d) 27:34

e) 61:26

## Ahhh. I was wondering what

Ahhh. I was wondering what "expenditure remains unchanged" meant.

I read it as still spending 3/5 of his salary (i.e., still saving 2/5 of his salary), whereas the answer choices tell me that he saves the same AMOUNT of money as he did previously (as opposed to the same FRACTION)

I have revised my above response accordingly.

## thank you!

## Here i made a slight mistake.

S-1: I have considered c=3a. and written as a:b:c = c/3:c/2:3a.. so insufficient.

S-2: I missed out 6*1=6 concept and chose B as sufficient.

Cant we consider c=3a in statement 1?

## For statement 1, you did

For statement 1, you did everything correctly to get c/3 : c/2 : 3a

From here, since we know c = 3a, we can take the last term above and replace 3a with c

When we do this we get c/3 : c/2 : c

To create an equivalent ratio, multiply all terms by 6 to get 2c : 3c : 6c

Divide all terms by c to get 2 : 3 : 6

## For statement 1 is it

## Partially. We also need the

Partially. We also need the fact that the other two variables (a and b) also appear in both fractions.

## Can I understand statement 1

Can I understand statement 1 as c:a = 1:3 and c:b= 1:2,

so a to c and c to b is 3:1:2

## That's not quite right.

That's not quite right.

The necessary property here says that k = k/1.

For example 3 = 3/1.

They've statement 1 says that c/a = 3.

This is the same as saying c/a = 3/1

Similarly, c:a = 3:1 (not 1:3)

The same applies to c/b = 2.

We can rewrite this as c/b = 2:1

In other words c:b = 2:1

Does that help?